Introduction to the special issue: comparing local refugee regimes - Schmiz, Antonie; Räuchle, Charlotte (ERDKUNDE, 2019)
The ‘local turn’ in migration studies has raised the question of how to study migration in cities of different size and power in various nation states. In conceptual terms, it has led to a rethinking of the local as a level of policymaking rather than merely focusing at national policies (Caponio et al. 2018). Frequently addressed topics range from migrant access to the labour and housing markets and educational facilities to anti-discrimination and diversity policies in local administrations, as well as migrant representation and not least, place-making at the neighbourhood scale (cf. Martiniello 2013; Bloemraad 2013). This scalar shift in migration studies also becomes visible in an increasing number of studies on refugees and asylum at the local scale. It is within local regimes that political conflicts around the issue of refugee reception become most palpable and where, for instance, the accommodation is organised and negotiated. Furthermore, municipal governments and locally organised civil society initiatives increasingly use their power to participate in the national and European processes of refugee distribution (see e.g. Seebrücke.org). However, it is still an open question to what extent these local refugee regimes share commonalities, or rather differ from one another. To date, only few systematic studies have adopted a comparative perspective on local refugee regimes and their entanglement with various administrative scales (Darling 2016; Steen 2016; Hinger et al. 2016). However, the comparative perspective forms a common denominator of all contributions in this special issue. It is not by accident that this issue, with its diverse set of perspectives from geography, sociology, history and anthropology, is published in a geographical journal. The discipline of geography has steadily contributed to the field of refugee studies, with about 50 research projects in Germany alone in the period from 2011 to 2016 (Kleist 2018, 21). Still, spatially comparative studies, whether synchronic or diachronic investigations– are still lacking, whereas the field is largely filled with single case studies and characterized by a fragmented production of scientific knowledge (Pott and Schmiz 2018). That is why this special issue makes a plea for strengthening theory building by re-conceptualising the local level in refugee studies through a relational comparative perspective from ‘comparative urbanism’ (Robinson 2011, 2016; Ward 2010). It enables a comparative study of migration and refugee regimes, also in small, rather peripheral cities and rural regions beyond major metropolitan gateway cities (Martiniello 2013). Furthermore, it facilitates the description, explanation and theorisation of local refugee regimes as they form in cities, provinces and nations (Ward 2010, 473). It acknowledges power asymmetries, migrant agency and the positionality of cities as posited by the ‘rescaling approach’ (Glick Schiller and Çağlar 2009). Moreover, a comparative urbanism perspective poses the question of how place-specific the production of local refugee regimes is. It thus lays the foundation for the discourse on the recognition of the local context (place matters!) and the analytical ‘local trap’ of conceptualising the city as the scale of reference. This translates into a critique of ‘methodological urbanism’ (Pott 2015) tied to the concept of ‘methodological nationalism’ (Wimmer and Glick Schiller 2002; Samers 2010). Lastly, comparative urbanism allows us to understand a local refugee regime as relationally produced rather than bounded and static, as problematized previously in migration studies (Brenner 2004). Complementary to comparative urbanism, the regime perspective serves as another theoretical framework of the special issue. It does not only allow an analysis of the involved state and non-state actors and their politics, as is the case in many governance analyses. Instead, the regime perspective focuses on negotiation processes, integrating migrant agency as part of the broader civil society into the debate of the local governance of migration (Tsianos and Karakayali 2010, 376; Hinger et al. 2016; Horvath et al. 2017; Pott et al. 2018). The special issue aims at initiating a thorough academic debate on local refugee regimes. In particular, the analysis of different administrative levels (supra-national, national and municipal) as well as of metropolitan and non-metropolitan contexts adds to the current theoretical debate on how asylum is regulated at the local scale and to what extent place-specific agency and actor networks influence these processes on the ground. This is highly topical in times of dynamic national political agendas towards refugees and an ongoing political and practical negotiation at the local scale. Therefore, with its focus on Germany, the issue enriches the academic debate with new insights from a national context in which the responsibilities for refugee accommodation ‘jump scales’ (Swyngedouw 1992).